2006
DOI: 10.1080/00319100500217819
|View full text |Cite
|
Sign up to set email alerts
|

Density, viscosity and thermodynamic activation for viscous flow of water+sulfolane

Abstract: Densities and viscosities for the system, water (W) þ sulfolane (SFL), have been determined for the entire range of composition at temperatures ranging from 303.15 to 323.15 K. Density, excess molar volume, viscosity, excess viscosity and thermodynamic activation parameters for viscous flow have been calculated and plotted against the mole fraction of SFL. The measured properties and some of the derived properties have been fitted to appropriate polynomial equations. These have been explained in terms of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Saleh et al [5] reported the atmospheric pressure densities and viscosities of water + sulfolane mixtures in the entire composition range at temperatures ranging from (303.15 to 323.15) K. Steele et al [6] reported heat capacity, vapor pressure, and density along the saturation line, measurements for cyclohexane-1-one, 1,2-dichloro-propane, 1,4-ditert-butylbenzene, (±)-2-ethylhexanoic, 2-(methylamino)ethanol, perfluoro-n-heptane, and sulfolane. Castagnolo et al [7] measured heat capacities of binary liquid mixtures of water-sulfolane and water-hexamethylphosphotriamide.…”
Section: Introductionmentioning
confidence: 98%
“…Saleh et al [5] reported the atmospheric pressure densities and viscosities of water + sulfolane mixtures in the entire composition range at temperatures ranging from (303.15 to 323.15) K. Steele et al [6] reported heat capacity, vapor pressure, and density along the saturation line, measurements for cyclohexane-1-one, 1,2-dichloro-propane, 1,4-ditert-butylbenzene, (±)-2-ethylhexanoic, 2-(methylamino)ethanol, perfluoro-n-heptane, and sulfolane. Castagnolo et al [7] measured heat capacities of binary liquid mixtures of water-sulfolane and water-hexamethylphosphotriamide.…”
Section: Introductionmentioning
confidence: 98%
“…∞ , and entropy Δ sol S m,x ∞ ) while moving from the gas standard state (perfect gas at working temperature T and pressure P t = p 0 = 0.1 MPa) to the solution standard state (infinitely diluted condition at working temperature T and pressure P COS → 0) were calculated and have been given in Table 5. The partial molar properties reflect quantitatively the 48,49 303.15−398 ρ SFL (g•cm −3 ) = −(8.8555 × 10 −4 )(T/K) + 1.53083 (R 2 = 0.9979) GBL 32 277.13−363.15 intermolecular interaction between gas and solvent in the liquid phase. The negative values of Δ sol H m,x ∞ show that the absorption of COS is an heat-releasing process, and the negative values of Δ sol S m,x ∞ mean that the solution become less chaotic than COS in the gas phase and this result is more significant in the (COS + SFL) system than that in (COS + GBL).…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…9 ,44,45 The liquid phase molar volume of GBL was taken from Han et al, 32 and its vapor pressure and critical properties (critical pressure, P c and critical temperature, T c ) were obtained from literature 46 as well. For the case of SFL, vapor pressure, 47 critical properties 47 and liquid phase molar volume 29,48,49 were obtained from reported data. 29,47−49 Mathematical relations of density and vapor pressure and the critical property values of the two pure liquids (SFL and GBL) have been summarized in Table 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative values of Dln g over the entire mole fraction range may be attributed mainly to the association between ETBE and ethoxyethanols molecules [1][2][3][4][11][12][13].…”
Section: Resultsmentioning
confidence: 99%